Fishing gear entanglement threatens recovery of critically endangered North Atlantic right whales. Issue 8 (14th June 2022) - Knowlton, Amy R.; Clark, James S.; Hamilton, Philip K.; Kraus, Scott D.; Pettis, Heather M.; Rolland, Rosalind M.; Schick, Robert S.
Abstract: North Atlantic right whales frequently become entangled in fishing gear, which can negatively affect their reproductive output and probability of survival. We estimated individual whale health from a hierarchical Bayesian model fit to photographic indices of health. We reviewed 696 whales sighted from 1980 to 2011 and assigned 1196 entanglement events to 573 individuals in six categories of increasing injury severity and estimated monthly median health scores (0–100 scale) for the duration of their life within the study period. We then quantified the relationship between entanglement injury events and their severity with survival, reproduction, and population health. Severe entanglements resulted in worse health for all whales—males and females with severe injuries were eight times more likely to die than males with minor injuries. Females with severe injuries that survived had the lowest birth rates. Though the relationship between entanglement and fecundity was complex, we found that as the health of reproductively active females declined, their calving intervals increased. Unimpacted whale health scores declined significantly over three decades, 1980s, 1990s, and 2000s, suggesting food limitations may be contributing to population‐wide health declines. Decadal health scores of entangled whales showed a more notable reduction in health suggesting a clear and perhaps synergistic effect.